2015
DOI: 10.1002/ar.23183
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Cerebral Fissure Anatomy Variations in Brachy‐, Dolicho‐ and Mesaticephalic Dogs and Their Importance to Brain Surgery

Abstract: The study used a sample of 69 formalin-fixed brains from adult dog cadavers (n 5 69) and aimed (1) to characterize the longitudinal cerebral fissure (LCF) anatomy in brachy-(B), dolicho-(D) and mesaticephalic-(M) dogs and their potential differences, and (2) to establish cranioencephalic relationships between the LCF and five classical craniometric points(cp): asterion(ast), bregma(b), stephanion(st), glabella(g), and pterion(pt). Anatomical records were collected using a digital caliper, and for statistical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
(51 reference statements)
1
3
0
Order By: Relevance
“…Inducing a brain adaptation to the vault architecture required compression in the dorsoventral axis, thus increasing the difficulty of identifying different brain regional structures. According to Schroeder et al, [36] brachycephalic breeds have larger LVVs than dolichocephalic and mesocephalic breeds [36][37][38][39][40][41]. Based on our results, age appears to influence the LVV in a statistically significant way, which Sue et al also found [42].…”
Section: Discussionsupporting
confidence: 78%
“…Inducing a brain adaptation to the vault architecture required compression in the dorsoventral axis, thus increasing the difficulty of identifying different brain regional structures. According to Schroeder et al, [36] brachycephalic breeds have larger LVVs than dolichocephalic and mesocephalic breeds [36][37][38][39][40][41]. Based on our results, age appears to influence the LVV in a statistically significant way, which Sue et al also found [42].…”
Section: Discussionsupporting
confidence: 78%
“…This selection acted directly on the brain itself, and also depended on the selective forces involved, promoting the decreasing size of one part of the brain in order to increase the size of another [ 35 , 37 ]. This is the result of simultaneous isocortical neurogenesis onset and terminal neurogenesis that varies substantially between the rostral and caudal poles in some species, allowing for disproportionate expansion of some encephalic cortical regions relative to others [ 38 , 39 , 40 , 41 , 42 , 43 ]. With the Bronson equation, it was possible to verify that D and B specimens presented the best ratio between the registered and the predicted BW, and according the study results, we found that D has the highest mean brain mass, heavier than the B and the M specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Images were exported in Neuroimaging Informatics Technology Initiative (NIfTI) format and were evaluated with MRIcron (freeware, http://people.cas.sc.edu/rorden/ mricron/index.html) and Thermo Scientific Amira for Life Sciences 6.0 software (https://www.fei.com/software). A detailed qualitative evaluation of shape, size, gyral patterns (Carreira & Ferreira, 2015a, 2015bEvans & de Lahunta, 2012;Kawamura & Naito, 1978), and ventricular anatomy was performed by a veterinary anatomist (KC) who assessed two-dimensional NIfTI-image series and threedimensional surface reconstructions generated from the brain MRIs, in order to select the one individual within this sample, which showed the most typical mesaticephalic brain conformation (Hussein et al, 2012;Milne et al, 2016) with no apparent structural disorders or unusual anatomical variations. After this analysis, the brain of a 7.5-year-old male Golden Retriever was chosen as a template for labeling.…”
Section: Methodsmentioning
confidence: 99%